Maier-Saupe nematogenic fluid with isotropic Yukawa repulsion at a hard wall: Mean field approximation - Holovko, M.; Patsahan, T.; Kravtsiv, I.; di Caprio, D. (Condensed Matter Physics, 2016)
The mean field approximation is formulated within the framework of the density field theory to study the properties of a Maier-Saupe nematogenic fluid near a hard wall. The density and the order parameter profiles are obtained using the analytical expressions derived in the linearized mean field approximation. The temperature dependencies of the contact values of the density and order parameter profiles are analyzed in detail. To estimate a validity of the applied approximations, the obtained theoretical results are compared with the original computer simulation data.